Modelamento da transformação de fases de aços de alta resistência microligados ao Nb durante resfriamento após laminação em tiras a quente - Antonio Adel dos Santos (2007)
Although equipments used in the steel industry are very large, specifications of shape, dimensions and mechanical properties of flat hot rolled products are very strict. An useful tool to help meet such specifications is the mathematical modelling of process, which can be used for either off line simulation or on line control. In hot strip rolling,the steel strip, after leaving the last rolling stand, is subjected first to a fast cooling on the run-out table and then to a slow cooling after coiling. During the cooling period, austenite decomposition takes place, this phenomenon playing an important role in the final mechanical properties as well as in the coiling temperature control, as this reaction is exothermic. Models for predicting the austenite transformation can be found in the literature, but they are usually limited to specific chemical compositions, often CMn steels, and none of such models takes into account the fact that the cooling rate is changed during the course of transformation. Thus, in this work, an integrated mathematical model for predicting the phase transformation of a commercial CMn steelmicroalloyed with Nb,V,Ti to meet the API-5L-X65 grade, has been developed. Intensive laboratory experiments using a Gleeble 3500 thermomechanical simulator were carried out to raise a database for the model development. The following variables influencing transformation were investigated: strain above and below the nonrecrystallizationtemperature; cooling rate down to coiling, and coiling temperature. Theintegrated model has the following submodels: (i) a model to predict the transformation start temperature, based on empirical formulae; (ii) a transformation kinetics model formulated by the Avrami equation conjugated with the additivity rule; (iii) prediction of volumetric phase fractions of ferrite and pearlite by using a mathematical procedure,in which pearlite formation starts when the carbon content of enriched austenite reaches the extrapolated Acm line under paraequilibrium conditions. The Avrami equation together with the additivity rule was able to describe the transformation even when two distinct cooling regimes were employed. This implies that the model can be applied to any cooling profile in industrial process. Besides, the application of the integrated model to processing conditions of the investigated steel has led to satisfactory predictions of microstructure and hardness observed in the coil. It has also been shown that the two cooling regimes must be considered in the model in order to predict the transformation properly, since the transformation of microalloyed steels advances overthe coiling process, different for the case of CMn steels.